Sterilization Policy with Incomplete Information in Peru: Does History Repeat Itself? - Bruno Jiménez; Silvio Rendon (Institute of Labor Economics (IZA), 2020)
We contrast the socio-demographic profiles and degree of information received by women that were sterilized with women that used other contraceptive methods. We use data from the 2016 round of the Demographic and Health Survey (DHS) for Peru and compare these profiles with those of the 2000s, which contain the effects of the massive non-voluntary sterilizations executed in Peru in the late 1990s. From 2000 to 2016 there is a reduction from 17% to 10% in the use of sterilization as a contraceptive method. There is also an important socio-demographic change in the incidence of sterilization, from women who are indigenous, from the highlands, and without electricity toward women who are non-indigenous, literate, coastal and who have electricity at home. There is not only no improvement in the information received by users of contraceptive methods with respect to the 1990s, but there is even a worsening: the percentage of sterilized women that received complete information dropped from 35% in 2000 to 34% in 2016. Moreover, the information provided for sterilizations continues to be poorer than for other, non-terminal, methods. We also estimate that providing incomplete information about the sterilization procedure increases the probability of sterilization in 7 percent points.
Keywords: J13; I15; J16; 330; health policy; fertility; sterilization; family planning; development